2016
DOI: 10.4103/2230-8210.176364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of underweight, overweight, and obesity among 2, 162 Brazilian school adolescents

Abstract: Introduction:The nutritional profile of the Brazilian population has changed in recent years. Therefore, this study aimed to assess the prevalence of nutritional status among Brazilian school adolescents during the period from January 2014 to December 2014.Methods:This study employed an observational design with a cohort of school adolescents. Anthropometric measurement was assessed by nutritionists in government schools. The cut-off points for body mass index according to Brazilian criteria for adolescents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study showed that 3.3% of the participants were underweight, 68% were normal, 18.2% were overweight, and 10.5% were obese which considered different from the prevalence of underweight, overweight, and obesity among adolescent girls in a study conducted by Silva and colleagues, which were 23%, 10.7% and 3.6% respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that 3.3% of the participants were underweight, 68% were normal, 18.2% were overweight, and 10.5% were obese which considered different from the prevalence of underweight, overweight, and obesity among adolescent girls in a study conducted by Silva and colleagues, which were 23%, 10.7% and 3.6% respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cut-offs are based on studies involving Western populations. According to this cutoff, the prevalence of obesity (≥30) is only 2–4% in Asian populations [ 22 ], while in young Brazilian adults the prevalence of obesity is 8.1% (males) and 10.7% (females) [ 23 ]. In addition, only genotype 1b patients were included in the Japanese cohort while in this study, genotypes 1a, 1b, and 3 were included that may have contributed to the differences in results.…”
Section: Discussionmentioning
confidence: 99%